2019
DOI: 10.1097/pgp.0000000000000513
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Chemotherapy Response Score (CRS) System for Tubo-Ovarian High-Grade Serous Carcinoma (HGSC)

Abstract: A chemotherapy response score (CRS) system was recently described to assess the histopathologic response and prognosis of patients with tubo-ovarian high-grade serous carcinoma (HGSC) receiving neoadjuvant chemotherapy. The current study was performed as an independent assessment of this CRS system. We retrospectively identified advanced stage HGSC patients who received neoadjuvant chemotherapy and underwent interval debulking. If available, a hemotoxylin and eosin slide from the omentum and the adnexa was sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 20 publications
8
46
1
Order By: Relevance
“…We retrieved 6 published papers and 5 met the inclusion criteria [7,[10][11][12][13]. 1 duplicate was removed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We retrieved 6 published papers and 5 met the inclusion criteria [7,[10][11][12][13]. 1 duplicate was removed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The International Collaboration on Cancer Reporting (ICCR) subsequently recommended the use of the CRS to assess histological NACT effect in HGSC to enable standardized and objective reporting [9]. Single institution retrospective studies have since reported an association between CRS and progression-free survival (PFS) but not OS [10][11][12][13]. These studies are limited by small sample sizes, lack of power to detect associations between CRS and OS, heterogeneity in participants, and the number of NACT cycles and regimens used.…”
Section: Introductionmentioning
confidence: 99%
“…For improving inter‐observer reproducibility of CRS, the training web site has been launched; furthermore, various external validation studies have confirmed the prognostic impact of CRS . However, assessment of CRS requires an appropriate number of sampling from the omentum and training of the scoring practice . In contrast, PWC has been already utilized in the daily practice of gynecologic surgery and needs no additional training or sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Reproducibility of CRS assignment between pathologists from different centres and with different levels of experience has been noted . In their study, Ditzel and colleagues noted that the interobserver agreement of the three‐tiered CRS scoring system was moderate, with a K ‐value of 0.48 at the first instance . After using the using the online tool available at Genetic Pathology Evaluation Centre (CRS: training website for the CRS system), the interobserver agreement improved to substantial with a K ‐value of 0.76.…”
Section: Crs In High Grade Serous Tubo‐ovarian Carcinoma (Hgsc)mentioning
confidence: 99%
“…17 In their study, Ditzel and colleagues noted that the interobserver agreement of the three-tiered CRS scoring system was moderate, with a K-value of 0.48 at the first instance. 11 After using the using the online tool available at Genetic Pathology Evaluation Centre (CRS: training website for the CRS system), 18 the interobserver agreement improved to substantial with a K-value of 0.76. The CRS2 category increased after the online training, drawing both from CRS1 and CRS3 categories.…”
Section: R E P R O D U C I B I L I T Y a N D V A L I D A T I O Nmentioning
confidence: 99%